Diversity of Antibiotic-Resistant Bacteria Identified from Intensive Shrimp Farming Areas in the Coastal Area of Kendal Regency - Narita Reci Kusuma; Sarjito Sarjito; Aninditia Sabdaningsih; Rosa Amalia; Sri Hastuti (Jurnal Kelautan Tropis, 2026)
Intensive Pennaeus vannamei aquaculture is a critical reservoir for the emergence of antimicrobial resistance (AMR), driven by the extensive use of antibiotics under high-density production conditions. This study aimed to isolate, characterize, and identify antibiotic-resistant bacteria from intensive shrimp pond environments in the Rowosari and Kaliwungu Districts of Kendal Regency, Central Java, Indonesia. Water, sediment, and shrimp samples were collected via purposive sampling and cultured on thiosulfate-citrate-bile salts sucrose (TCBS) and Zobell Marine Agar. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion method, following CLSI guidelines, against erythromycin (ERY), oxytetracycline (OXY), enrofloxacin (ENR), and amoxicillin (AMX). Molecular identification was conducted via 16S rRNA gene sequencing with BLAST homology analysis and neighbor-joining phylogenetic reconstruction using MEGA-X. Four isolates were recovered and characterized in this study. Oxytetracycline resistance was detected universally, and isolate A23 exhibited complete resistance to all tested antibiotics. Molecular analysis identified A23 as V. injensis strain VS1, B15 as V. metschnikovii strain Vm-4, and B12 and B17 as Staphylococcus arlettae, each with 100% sequence homology with reference strains. These findings confirm the presence of diverse AMR bacterial assemblages in intensive shrimp pond environments in Kendal Regency and underscore the critical need for integrated AMR surveillance and prudent antibiotic stewardship in Indonesian shrimp aquaculture.